KrCl and XeCl excilamps and LP-Hg lamp for UV and UV/H2O2 decolourization of dyes in water (2020)
In the present study, the decolourization efficiencies of LP-Hg lamp, XeCl and KrCl excilamps at the same power density were compared for the decolourization of dyes in water by UV and UV/H2O2 processes in a batch reactor. Laboratory prototypes of XeCl and KrCl excilamps and a commercial LP-Hg lamp were studied as UV sources. Methylene Blue and Eliamine Blue dyes were used as model pollutants. The effect of the initial concentrations of dye and H2O2 in the TOC removal and kinetic parameters were also studied. The ratio of dye decolourization to the electric power consumption of the KrCl excilamp and LP-Hg lamp for the decolourization of Methylene Blue and Eliamine Blue were evaluated. As a result, the KrCl excilamp showed significantly higher decolourization efficiencies than LP-Hg lamp and XeCl excilamp, but the dye removal rate was significantly slower for Methylene Blue than for Eliamine Blue with this lamp. The KrCl lamp can be an alternative to conventional LP-Hg lamp for the decolourization of dyes by photodegradation, but it depends on the type of dye treated. The addition of H2O2 in a concentration between 0.05 and 0.09%v/v increases significantly the efficiency of the decolourization of Methylene Blue, and further increase does not lead to a higher increase in conversion. The experimental data were fitted to the one phase decay kinetic model with good agreement and the kinetic parameters were reported. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.